Association between ‘Emergency obstetric & newborn care readiness’ and delivery service utilization in Bangladesh: Evidence from national health facility assessment surveys - Kaji Keya-Korotki; Nabil Natafgi; Mark Macauda; Syed Abdul Hamid; M. Mahmud Khan (PLoS ONE, 2025)
Background Bangladesh faces one of the highest global burdens of maternal and newborn deaths, primarily caused by hemorrhage and eclampsia/preeclampsia. Despite reducing maternal mortality by 40%, comprehensive medical interventions remain insufficient in health facilities. Objectives This study assessed the readiness of sub-district hospitals in Bangladesh to provide Emergency Obstetric and Newborn Care (EmONC) and analyzed the association between facility readiness and delivery rates. Methods Using Health Facility Assessment Survey data from 140 hospitals in 2014 and 141 in 2017, facility readiness was measured based on nine signal functions: administering antibiotics, oxytocin, and anticonvulsants; providing blood transfusions; performing cesarean and assisted vaginal deliveries; managing retained placentas and products of conception; and neonatal resuscitation. Donabedian’s model guided the analysis. Multiple linear regression examined associations between facility readiness and delivery rates using 2017 data. Results Between 2014 and 2017, the availability of signal functions such as oxytocin (85% to 95%), anticonvulsants (58% to 63%), and blood transfusions (22% to 38%) improved. In 2014, 77% of facilities had at least 5 signal functions, 49% had 7, and 6% had all 9. By 2017, these increased to 83%, 56%, and 8%, respectively. Despite these improvements, the mean readiness index remained nearly unchanged (0.67 in 2014 vs. 0.69 in 2017). Only 8% of facilities performed fewer than 52 deliveries annually in 2017, while 26% conducted over 500. Regression analysis revealed a significant association between readiness scores and delivery rates (p =  0.009). Conclusion While certain indicators improved, overall readiness stagnated due to shortages of anesthetists, gynecologists, and essential supplies. With 64% of surveyed sub-district hospitals classified as comprehensive care facilities, resource and staffing investments are crucial to enhance readiness and reduce maternal and newborn mortality.